Effect of Laser Acupuncture on Disuse Osteoarthritis: An Ultrasound Biomicroscopic Study of Patellar Articular Cartilage in Rats. (19th July 2012) - Wang, Qing; Guo, Xia; Liu, Mu-Qing; Wang, Xiao-Yun; Zheng, Yong-Ping
Abstract : To investigate the effect of laser acupuncture (LA) on disuse changes in articular cartilage using ultrasound biomicroscopy (UBM), Eighteen rats were randomly divided into the control group (C), the tail-suspended group (T), and the tail-suspended with LA treatment group (L). During 28-day suspension period, group L were treated with LA at acupoints on the left hindlimb while group T had a sham treatment. Ultrasound roughness index (URI), integrated reflection coefficient (IRC), integrated backscatter coefficient (IBC), cartilage thickness, and ultrasonographic score (US) of articular cartilage at patella were measured by using an ultrasound biomicroscopy system (UBS). Compared with the group C, URI significantly (P < 0.01 ) increased by 60.9% in group T, increased by 38.1% in group L. In addition, unloading induced a significant cartilage thinning (P < 0.05 ) in group T, whereas cartilage thickness in group L was 140.22 ± 19.61 μ m reaching the level of the control group (147.00 ± 23.99 μ m). There was no significant difference in IRC, IBC, and US among the three groups. LA therapy could help to retain the quality of articular cartilage which was subjected to unloading. LA would be a simple and safe nonpharmacological countermeasure for unloading-induced osteoarthritis. The UBM system has potential to be a sensitive, specific tool for quantitative assessment of articular cartilage.